Hexose Potentiates Peptide-Conjugated Morpholino Oligomer Efficacy in Cardiac Muscles of Dystrophic Mice in an Age-Dependent Manner - Gang Han; Ben Gu; Caorui Lin; Hanhan Ning; Jun Song; Xianjun Gao; Hong M. Moulton; HaiFang Yin (Elsevier, 2019)
Insufficient delivery of oligonucleotides to muscle and heart remains a barrier for clinical implementation of antisense oligonucleotide (AO)-mediated exon-skipping therapeutics in Duchenne muscular dystrophy (DMD), a lethal monogenic disorder caused by frame-disrupting mutations in the DMD gene. We previously demonstrated that hexose, particularly an equal mix of glucose:fructose (GF), significantly enhanced oligonucleotide delivery and exon-skipping activity in peripheral muscles of mdx mice; however, its efficacy in the heart remains limited. Here we show that co-administration of GF with peptide-conjugated phosphorodiamidate morpholino oligomer (PPMO, namely, BMSP-PMO) induced an approximately 2-fold higher level of dystrophin expression in cardiac muscles of adult mdx mice compared to BMSP-PMO in saline at a single injection of 20 mg/kg, resulting in evident phenotypic improvement in dystrophic mdx hearts without any detectable toxicity. Dystrophin expression in peripheral muscles also increased. However, GF failed to potentiate BMSP-PMO efficiency in aged mdx mice. These findings demonstrate that GF is applicable to both PMO and PPMO. Furthermore, GF potentiates oligonucleotide activity in mdx mice in an age-dependent manner, and, thus, it has important implications for its clinical deployment for the treatment of DMD and other muscular disorders. Keywords: hexose, peptide-conjugated morpholino oligomer, Duchenne muscular dystrophy, exon skipping, cardiac functions